Berpikir kombinatorik matematis siswa dalam mengkonstruksi konsep peluang - Jepri Igo Budi Handoko; Eko Nisfu Umar Singgih; Wharyanti Ika Purwaningsih (Jurnal Inovasi Pendidikan Matematika (JIPM), 2019)
This qualitative research aims to describe activity of students mathematical combinatorial thinking in constructing of the opportunity concept. The subject of the study is two students of Junior High School who had the ability in constructing concept. Data collection was obtained at the time of learning carried out based on learning plan as research instruments. The results showed a combinatorial thinking activity in constructing concepts. Counting processes are showen by students identifying dice and coins, solving theoritical opportunities problems with tables or diagrams, and solving empirical opportunities problems. Formulas/exspressions are showen by students being able to construct sampel points and sample space, construct theoritical opportunities concept, and make mathematical formulas of opportunities. Set of outcomes is showen by students being able to find the results of solving theoritical opportunity problems of one/or more dice and coins as well as the results of solving empirically opportunity problems.